PENGARUH REBRANDING CALON PRESIDEN PRABOWO SUBIANTO DI MEDIA SOSIAL TIKTOK TERHADAP TINGKAT KEPERCAYAAN DAN PARTISIPASI PEMILIH GENERASI Z PADA PEMILU 2024 KOTA MAGELANG - Suryanti, Suryanti; Fikry, Debby Salju; Putri, Wahyu Eka; Ramadhan, Syahrul Bastian; Kusuma, Febryan Jati (LPPM-PMP Universitas Tidar, 2024)
The dominant involvement of generation Z in the 2024 elections is a big highlight for Indonesia. Especially in Magelang City, generation Z occupies the second position with the most voters in the 2024 elections and has a big influence on a candidate's vote share. Social media is the most important platform for generation Z to influence and participate in elections. Social media, especially TikTok, has become an important tool in political campaigns, especially for Presidential Candidate Prabowo Subianto who is rebranding through this platform. This research aims to determine the effect of Prabowo Subianto's rebranding on the level of trust and participation of generation Z voters in Magelang City. The research method used is quantitative, where numerical data is collected through surveys and statistical analysis. The research results show that Prabowo Subianto's rebranding has a significant effect on the level of trust and participation of generation Z in the 2024 election.